Latvijskaâ nalogovaâ sistema v kontekste integracii v Evropejskij Soûz - Paberza, Inese (The Latvian Tax System in the Context of Integration into the European Union, 2005)
The present report provides an insight to the basic issues of harmonization of the Latvian tax system with regard to EU directives. The following taxes are reviewed, individually - personal income tax, corporate income tax, natural resources tax, social tax, real estate tax, VAT. In the context of the aforementioned taxes, the existing tax rates in EU countries and application conditions for those rates are outlined, as well as, in certain cases, the taxes existing in EU member states from the point of view of EU directives are explored.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 478-486